Catastrophe Insurance Programs for Public Assets : Operational Framework - World Bank (World Bank, Washington, DC, 2020)
Natural disasters in APEC (Asia-Pacific Economic Cooperation) economies have significant impacts on the economy and daily lives of the population. To minimize those impacts, a comprehensive policy package is required, which covers the key strands of prevention, preparedness and response. The establishment of an insurance scheme to support the financial protection of public assets against disasters can form an important part of this package, alongside the use of complementary financial instruments within a broader disaster risk financing strategy, and investments in quality, resilient infrastructure and buildings to prevent losses. This report aims to synthesize peer-to-peer learning among APEC economies into a document that provides useful, practical guidance to finance officials about the design and implementation of catastrophe risk insurance programs for public assets based on case studies of APEC economies and beyond.